Band alignment at InP/TiO2 interfaces from density-functional theory - Ruiz Alvarado, Isaac Azahel; Dreßler, Christian; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
Abstract The natural band alignments between indium phosphide and the main dioxides of titanium, i.e. rutile, anatase, and brookite as well as amorphous titania are calculated from the branch-point energies of the respective materials. Irrespective of the titania polymorph considered, type-I band alignment is predicted. This may change, however, in dependence on the microscopic interface structure: supercell calculations for amorphous titania grown on P-rich InP(001) surfaces result in a titania conduction band that nearly aligns with that of InP. Depending on the interface specifics, both type-I band and type-II band alignments are observed in the simulations. This agrees with recent experimental findings.

Integration of Multijunction Absorbers and Catalysts for Efficient Solar‐Driven Artificial Leaf Structures: A Physical and Materials Science Perspective - Hannappel, Thomas; Shekarabi, Sahar; Jaegermann, Wolfram; Runge, Erich; Hofmann, Jan Philipp; van de Krol, Roel; May, Matthias M.; Paszuk, Agnieszka; Hess, Franziska; Bergmann, Arno; Bund, Andreas; Cierpka, Christian; et al. (Solar RRL)
Artificial leaves could be the breakthrough technology to overcome the limitations of storage and mobility through the synthesis of chemical fuels from sunlight, which will be an essential component of a sustainable future energy system. However, the realization of efficient solar‐driven artificial leaf structures requires integrated specialized materials such as semiconductor absorbers, catalysts, interfacial passivation, and contact layers. To date, no competitive system has emerged due to a lack of scientific understanding, knowledge‐based design rules, and scalable engineering strategies. Herein, competitive artificial leaf devices for water splitting, focusing on multiabsorber structures to achieve solar‐to‐hydrogen conversion efficiencies exceeding 15%, are discussed. A key challenge is integrating photovoltaic and electrochemical functionalities in a single device. Additionally, optimal electrocatalysts for intermittent operation at photocurrent densities of 10–20 mA cm −2 must be immobilized on the absorbers with specifically designed interfacial passivation and contact layers, so‐called buried junctions. This minimizes voltage and current losses and prevents corrosive side reactions. Key challenges include understanding elementary steps, identifying suitable materials, and developing synthesis and processing techniques for all integrated components. This is crucial for efficient, robust, and scalable devices. Herein, corresponding research efforts to produce green hydrogen with unassisted solar‐driven (photo‐)electrochemical devices are discussed and reported.

DFT‐Assisted Investigation of the Electric Field and Charge Density Distribution of Pristine and Defective 2D WSe2 by Differential Phase Contrast Imaging - Groll, Maja; Bürger, Julius; Caltzidis, Ioannis; Jöns, Klaus D.; Schmidt, Wolf Gero; Gerstmann, Uwe; Lindner, Jörg K. N. (Small)
Abstract Most properties of solid materials are defined by their internal electric field and charge density distributions which so far are difficult to measure with high spatial resolution. Especially for 2D materials, the atomic electric fields influence the optoelectronic properties. In this study, the atomic‐scale electric field and charge density distribution of WSe 2 bi‐ and trilayers are revealed using an emerging microscopy technique, differential phase contrast (DPC) imaging in scanning transmission electron microscopy (STEM). For pristine material, a higher positive charge density located at the selenium atomic columns compared to the tungsten atomic columns is obtained and tentatively explained by a coherent scattering effect. Furthermore, the change in the electric field distribution induced by a missing selenium atomic column is investigated. A characteristic electric field distribution in the vicinity of the defect with locally reduced magnitudes compared to the pristine lattice is observed. This effect is accompanied by a considerable inward relaxation of the surrounding lattice, which according to first principles DFT calculation is fully compatible with a missing column of Se atoms. This shows that DPC imaging, as an electric field sensitive technique, provides additional and remarkable information to the otherwise only structural analysis obtained with conventional STEM imaging.

Ultrafast Electron Dynamics at the P‐rich Indium Phosphide/TiO2 Interface - Diederich, Jonathan; Rojas, Jennifer Velazquez; Paszuk, Agnieszka; Pour, Mohammad Amin Zare; Höhn, Christian; Ruiz Alvarado, Isaac Azahel; Schwarzburg, Klaus; Ostheimer, David; Eichberger, Rainer; Schmidt, Wolf Gero; Hannappel, Thomas; van de Krol, Roel; et al. (Advanced Functional Materials)
Abstract The current efficiency records for generating green hydrogen via solar water splitting are held by indium phosphide (InP)‐based photo‐absorbers, protected by TiO 2 layers grown through atomic layer deposition (ALD). InP is also a leading material for photonic integrated circuits and computing, where ultrafast near‐surface behavior is key. A previous study described electronic pathways at the phosphorus‐rich (P‐rich) surface of p‐doped InP(100) using time‐resolved two‐photon photoemission (tr‐2PPE) spectroscopy. Here, the intricate electron pathways of the P‐rich InP surface modified with ALD‐deposited TiO 2 are explored. Photoexcited bulk InP electrons migrate through a bulk‐to‐surface transition cluster of states and surface states and inject into the TiO 2 conduction band (CB). Energy levels and occupation dynamics of CB states in P‐rich InP and TiO 2 adlayers are observed, with discrete states preserved up to 10 nm TiO 2 deposition. Thermalization lifetimes of excited electrons > 0.8 eV above the InP conduction band minimum (CBM) are preserved for layer thicknesses up to 2.5 nm. Annealing at 300 °C to achieve crystalline TiO 2 reconstructions destroys interfacial states, affecting charge transfer. These observations enable innovative engineering of the P‐rich InP/TiO 2 heterointerface, opening new possibilities for studying hot‐carrier extraction, adsorbate effects, surface plasmons, and improving photovoltaic and PEC water‐splitting devices.

Relativistic calculation of the orbital hyperfine splitting in complex microscopic structures - Franzke, Katharina; Schmidt, Wolf Gero; Gerstmann, Uwe (Journal of Physics: Conference Series)
Abstract Theoretical spectroscopy based on double perturbation theory is typically challenged by systems with large orbital hyperfine splitting. Therefore, we here derive a rigorous, non-perturbative scheme starting from Dirac’s equation which allows to calculate the contribution of the orbital HFI for complex structures including heavy atoms with strong spin-orbit coupling (SOC). Using the PAW formalism, the method has been implemented in the software package Quantum ESPRESSO. We show that the ‘orbital part’ actually scales with SOC strength if orbital quenching is hindered by low local symmetry, i.e. in case of dimers or atoms at surfaces. This holds true in particular when the unpaired electron is localized in quasi-atomic p -like orbitals. Here, the orbital part is by far not negligible, but becomes dominant by surpassing the dipolar contribution by a factor of five.

Unraveling Electron Dynamics in p-type Indium Phosphide (100): A Time-Resolved Two-Photon Photoemission Study - Diederich, Jonathan; Velasquez Rojas, Jennifer; Zare Pour, Mohammad Amin; Ruiz Alvarado, Isaac Azahel; Paszuk, Agnieszka; Sciotto, Rachele; Höhn, Christian; Schwarzburg, Klaus; Ostheimer, David; Eichberger, Rainer; Schmidt, Wolf Gero; Hannappel, Thomas; et al. (Journal of the American Chemical Society)

Substrate Doping and Defect Influence on P-Rich InP(001):H Surface Properties - Sciotto, Rachele; Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero (Surfaces)
Density-functional theory calculations on P-rich InP(001):H surfaces are presented. Depending on temperature, pressure and substrate doping, hydrogen desorption or adsorption will occur and influence the surface electronic properties. For p-doped samples, the charge transition levels of the P dangling bond defects resulting from H desorption will lead to Fermi level pinning in the lower half of the band gap. This explains recent experimental data. For n-doped substrates, H-deficient surfaces are the ground-state structure. This will lead to Fermi level pinning below the bulk conduction band minimum. Surface defects resulting from the adsorption of additional hydrogen can be expected as well, but affect the surface electronic properties less than H desorption.

Atomic wires on substrates: Physics between one and two dimensions - Pfnür, H.; Tegenkamp, C.; Sanna, S.; Jeckelmann, E.; Horn-von Hoegen, M.; Bovensiepen, U.; Esser, N.; Schmidt, Wolf Gero; Dähne, M.; Wippermann, S.; Bechstedt, F.; Bode, M.; et al. (Surface Science Reports)

Defect-Assisted Exciton Transfer across the Tetracene-Si(111):H Interface - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review Letters)

Time-bin entanglement in the deterministic generation of linear photonic cluster states - Bauch, David; Köcher, Nikolas; Heinisch, Nils; Schumacher, Stefan (APL Quantum)
We theoretically investigate strategies for the deterministic creation of trains of time-bin entangled photons using an individual quantum emitter described by a Λ-type electronic system. We explicitly demonstrate the theoretical generation of linear cluster states with substantial numbers of entangled photonic qubits in full microscopic numerical simulations. The underlying scheme is based on the manipulation of ground state coherences through precise optical driving. One important finding is that the most easily accessible quality metrics, the achievable rotation fidelities, fall short in assessing the actual quantum correlations of the emitted photons in the face of losses. To address this, we explicitly calculate stabilizer generator expectation values as a superior gauge for the quantum properties of the generated many-photon state. With widespread applicability in other emitter and excitation–emission schemes also, our work lays the conceptual foundations for an in-depth practical analysis of time-bin entanglement based on full numerical simulations with predictive capabilities for realistic systems and setups, including losses and imperfections. The specific results shown in the present work illustrate that with controlled minimization of losses and realistic system parameters for quantum-dot type systems, useful linear cluster states of significant lengths can be generated in the calculations, discussing the possibility of scalability for quantum information processing endeavors.

Charge transfer magnetoexcitons in magnetoabsorption spectra of asymmetric type-II double quantum wells - Röder, J.; Gerhard, M.; Fuchs, C.; Stolz, W.; Heimbrodt, W.; Koch, M.; Ngo, C.; Steiner, J. T.; Meier, Torsten (Physical Review B)

Experimental retrieval of photon statistics from click detection - Krishnaswamy, Suchitra; Schlue, Fabian; Ares, L.; Dyachuk, V.; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Floquet dynamics of ultracold atoms in optical lattices with a parametrically modulated trapping potential - Ali, Usman; Holthaus, Martin; Meier, Torsten (New Journal of Physics)
Abstract Experiments with ultracold atoms in optical lattices usually involve a weak parabolic trapping potential which merely serves to confine the atoms, but otherwise remains negligible. In contrast, we suggest a different class of experiments in which the presence of a stronger trap is an essential part of the set-up. Because the trap-modified on-site energies exhibit a slowly varying level spacing, similar to that of an anharmonic oscillator, an additional time-periodic trap modulation with judiciously chosen parameters creates nonlinear resonances which enable efficient Floquet engineering. We employ a Mathieu approximation for constructing the near-resonant Floquet states in an accurate manner and demonstrate the emergence of effective ground states from the resonant trap eigenstates. Moreover, we show that the population of the Floquet states is strongly affected by the phase of a sudden turn-on of the trap modulation, which leads to significantly modified and rich dynamics. As a guideline for further studies, we argue that the deliberate population of only the resonance-induced effective ground states will allow one to realize Floquet condensates which follow classical periodic orbits, thus providing challenging future perspectives for the investigation of the quantum–classical correspondence.

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, D.; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Structural fingerprints in the reflectance anisotropy of AlInP(001) - Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Hannappel, Thomas; Schmidt, Wolf Gero (Physical Review B)

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
Keywords: General Physics and Astronomy

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.

Structural and Electrochemical Properties of F-Doped RbTiOPO4 (RTP:F) Predicted from First Principles - Bocchini, Adriana; Xie, Yingjie; Schmidt, Wolf Gero; Gerstmann, Uwe (Crystals)
Batteries based on heavier alkali ions are considered promising candidates to substitute for current Li-based technologies. In this theoretical study, we characterize the structural properties of a novel material, i.e., F-doped RbTiOPO4 (RbTiPO4F, RTP:F), and discuss aspects of its electrochemical performance in Rb-ion batteries (RIBs) using density functional theory (DFT). According to our calculations, RTP:F is expected to retain the so-called KTiOPO4 (KTP)-type structure, with lattice parameters of 13.236 Å, 6.616 Å, and 10.945 Å. Due to the doping with F, the crystal features eight extra electrons per unit cell, whereby each of these electrons is trapped by one of the surrounding Ti atoms in the cell. Notably, the ground state of the system corresponds to a ferromagnetic spin configuration (i.e., S=4). The deintercalation of Rb leads to the oxidation of the Ti atoms in the cell (i.e., from Ti3+ to Ti4+) and to reduced magnetic moments. The material promises interesting electrochemical properties for the cathode: rather high average voltages above 2.8 V and modest volume shrinkages below 13% even in the fully deintercalated case are predicted.

14N Hyperfine and nuclear interactions of axial and basal NV centers in 4H-SiC: A high frequency (94 GHz) ENDOR study - Murzakhanov, F. F.; Sadovnikova, M. A.; Mamin, G. V.; Nagalyuk, S. S.; von Bardeleben, H. J.; Schmidt, Wolf Gero; Biktagirov, Timur; Gerstmann, Uwe; Soltamov, V. A. (Journal of Applied Physics)
The nitrogen-vacancy (NV) centers (NCVSi)− in 4H silicon carbide (SiC) constitute an ensemble of spin S = 1 solid state qubits interacting with the surrounding 14N and 29Si nuclei. As quantum applications based on a polarization transfer from the electron spin to the nuclei require the knowledge of the electron–nuclear interaction parameters, we have used high-frequency (94 GHz) electron–nuclear double resonance spectroscopy combined with first-principles density functional theory to investigate the hyperfine and nuclear quadrupole interactions of the basal and axial NV centers. We observed that the four inequivalent NV configurations (hk, kh, hh, and kk) exhibit different electron–nuclear interaction parameters, suggesting that each NV center may act as a separate optically addressable qubit. Finally, we rationalized the observed differences in terms of distinctions in the local atomic structures of the NV configurations. Thus, our results provide the basic knowledge for an extension of quantum protocols involving the 14N nuclear spin.